(untitled) (Homoeopathy for All, 2024)
Infertility is considered a condition in which a woman is unable to become pregnant despite having regular intercourse for more than 12 months without the use of birth control pills and condoms. The incidence of infertility is increasing worldwide due to many factors such as ovulatory problem, oligospermia, diabetes, pituitary factors nutrition, lifestyle, hormonal health factors and environmental factors. Infertility has psychological and social impact. According to research, approximately one in six couples are infertile. Here homeopathic medicines help in pregnancy by eliminating or by curing the disease, there are many things we can control but when all the tests are normal and no causes are found homeopathic medicine plays an important role in this because sometimes homeopathic medicine works on the symptoms which are obstacles in pregnancy. It may be occurring due to per vaginal discharge, irregular menstrual bleeding, erectile dysfunction homeopathy plays an important role to manage this condition.